2022
DOI: 10.1049/mna2.12142
|View full text |Cite
|
Sign up to set email alerts
|

Melamine sponge decorated with Fe 3 O 4 /CuS nanoparticles as novel peroxidase‐like nanozyme for disinfection

Abstract: A melamine sponge‐supported Fe3O4/CuS nanozyme with highly peroxidase‐like activity was fabricated using polydopamine (PDA) as adsorption agent (named as S/PDA/Fe3O4/CuS). Fe3O4 and CuS nanoparticles were well dispersed on the surface of melamine sponge. Effects of reaction parameters such as temperature and solution pH on peroxidase‐like activity were investigated. S/PDA/Fe3O4/CuS exhibited highly disinfection efficiency against both Escherichia coli and Staphylococcus aureus in the presence of trace H2O2 (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…According to figure 5(c), the degradation rate of methyl orange increased with the rising H2O2 concentration. Nonetheless, it was also found that addition of only a small amount of H2O2 could produce a great impact on the photocatalytic degradation rate of methyl orange [11]. Since H2O2 is a strong oxidizing agent, the primary purpose of its incorporation into the photocatalyst system is to promote the complete degradation of methyl orange [12].…”
Section: Effects Of Process Parameters On Methyl Orange Degradation Ratementioning
confidence: 99%
“…According to figure 5(c), the degradation rate of methyl orange increased with the rising H2O2 concentration. Nonetheless, it was also found that addition of only a small amount of H2O2 could produce a great impact on the photocatalytic degradation rate of methyl orange [11]. Since H2O2 is a strong oxidizing agent, the primary purpose of its incorporation into the photocatalyst system is to promote the complete degradation of methyl orange [12].…”
Section: Effects Of Process Parameters On Methyl Orange Degradation Ratementioning
confidence: 99%